Design And Development of An IoT-Based Automatic Magnetic Balance Testing Device for Three-Phase Transformers at PT. Bambang Djaja - Kharisma Aji Saputra Wardani; Miftahur Rohman (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2026)
Magnetic Balance testing on three-phase transformers that are still done manually has the potential to cause human error and delays in defect identification. This research aims to develop an automatic Magnetic Balance testing tool based on the Internet of Things (IoT) using Arduino Mega 2560 microcontroller and Wemos D1 mini (ESP8266) connected to Google Spreadsheet as an online data logger. Voltage regulation on each phase is done automatically through a relay, while the measurement results are displayed on the LCD and recorded in real-time to the Spreadsheet. Based on the test results, the device functions properly and meets the Magnetic Balance testing standards, this is evidenced when we test one of the phases, the voltage value read in the other two phases when summed is close to or in accordance with the phase that is given a voltage. The successful integration of the system with Spreadsheet allows remote monitoring of test results and supports early detection of potential transformer damage. Keywords: Arduino Mega 2560, Google Spreadsheet, Internet of Things, Magnetic Balance, Wemos D1 mini ESP8266.